Financial Intermediation in a Less Developed Economy: The History of the United Bank of India - Mallick, Indrajit; Marjit, Sugata (New Delhi: Sage, 2008)
Financial Intermediation in a Less Developed Economy is an institutional narrative of a bank in a developing economy which acts as a case study and brings out the essential relationship between finance and economic development. The volume defines the financial intermediary organization and relates it to the process of economic development. In the process the authors argue that the conventional models of banking constructed for developed countries need to be complemented by institutional narratives of banking that focus on minimization of the transaction costs of finance and organization.
The roots -- Banking crisis and the merger -- Poat-merger developments (1950-1969) -- Nationalization and the organizational challenge -- The years of development banking -- The crisis years (1985-2000) -- The recovery and beyond
Keywords: Banks and Banking -- India; United Bank of India (Calcutta, India); Intermediation (Finance) -- India